Development of Multimultural PKN Interactive Learning Multimedia Development in Class IV SD IT NU Tanjung Morawa Academic Year 2018/2019 - Surahmawati Dwi Ririn; Reh Bungana Br Perangin-Angin; R. Mursid (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The purpose of this study was to determine the feasibility of multicultural-based interactive learning multimedia used in thematic learning at SD IT NU Tanjung Morawa and determine the effectiveness of the use of multicultural-based interactive learning multimedia used in thematic learning at SD IT NU Tanjung Morawa. The subjects of this study were the fourth grade students at SD IT NU Tanjung Morawa in 20118/2019, amounting to 30 people. As the object of this research is learning media, the scale of students' responses to learning media and student learning outcomes tests. The development model that will be used to develop learning media tools in this study is the Thiagarajan model known as the Four-D (Model 4-D). The 4-D model was chosen because it is systematic and appropriate for developing learning tools. The results of the study are multicultural-based interactive learning media that is used in the fourth grade thematic learning at SD IT NU Tanjung Morawa. multicultural-based interactive learning media used in class IV thematic learning at SD IT NU Tanjung Morawa effectively used.